Implementasi Literasi Informasi di Sekolah - Mashur, Ilham (Pustakaloka, 2012)
Lately the term information literacy is often discussed this awareness need to be appreciated. Even in Indonesia it can be said to be late, but considering the importance of the benefits of information for the developments of the awareness that literacy should be developed. Information literacy is defined is one knowledge of the needs information, the ability to identify, seek, evaluate, organize and effectively create, use and communicate information for solving problems.